Journal of Diabetes and Clinical Research 2020
DOI: 10.33696/diabetes.1.024
|View full text |Cite
|
Sign up to set email alerts
|

Improved Wound Closure Rates and Mechanical Properties Resembling Native Skin in Murine Diabetic Wounds Treated with a Tropoelastin and Collagen Wound Healing Device

Abstract: Chronic wounds in patients suffering from type II diabetes mellitus (DMII) where wounds remain open with a complicated pathophysiology, healing, and recovery process is a public health concern. Normal wound healing plays a critical role in wound closure, restoration of mechanical properties, and the biochemical characteristics of the remodeled tissue. Biological scaffolds provide a tissue substitute to help facilitate wound healing by mimicking the extracellular matrix (ECM) of the dermis. In the current study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…In vitro and in vivo experiments demonstrated that PVA/EPP1 fiber scaffolds accelerated wound repair in diabetic mice. Kellar et al (2020) investigated the synthesis of electrospun biomimetic scaffolds containing Tropoelastin (TE) and collagen. In vivo experiments using a diabetic mouse model revealed that the scaffold group exhibited increased neoplastic skin tissue, faster wound healing, reduced inflammatory response, and closer resemblance to unwounded skin compared to the control group.…”
Section: Application Of Electrospun Scaffolds For Diabetic Foot Ulcersmentioning
confidence: 99%
“…In vitro and in vivo experiments demonstrated that PVA/EPP1 fiber scaffolds accelerated wound repair in diabetic mice. Kellar et al (2020) investigated the synthesis of electrospun biomimetic scaffolds containing Tropoelastin (TE) and collagen. In vivo experiments using a diabetic mouse model revealed that the scaffold group exhibited increased neoplastic skin tissue, faster wound healing, reduced inflammatory response, and closer resemblance to unwounded skin compared to the control group.…”
Section: Application Of Electrospun Scaffolds For Diabetic Foot Ulcersmentioning
confidence: 99%
“…At this stage, fibroblasts mainly secrete type III collagen, forming granulation tissue. Furthermore, fibroblasts can differentiate into myofibroblasts, which have the contractile capacity to reach the wound edges, besides neoangiogenesis results in the vascularization of the dermis and the proliferation of keratinocytes favors the re-epithelialization and closure of the epidermis [ 5 7 ]. The remodeling phase is characterized by extracellular matrix remodeling, replacing scar tissue with a physiological matrix, constituted mainly of Col I [ 6 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%